“Our Theater,” in Performance - Debra Castillo (Studies in 20th & 21st Century Literature, 2008)
The final chapter of Miguel Rubio Zapata’s El cuerpo ausente (performance político) ‘Absent body (political performance)’ begins with an epigraph from Antonin Artaud, at first glance a very unexpected inspiration for a group famed for its politically-charged performances...
Keywords: Miguel Rubio Zapata; El cuerpo ausente (performance político); Absent body (political performance); Antonin Artaud